Efek Esterifikasi Gugus -Oh Senyawa (2,5-Bis(4-Hidroksi-3-Metoksibenzilidin)-Siklopentanon) Dan (2,5-Bis(4-Hidroksi -3,5-Dimetil)-Benzilidinsiklopentanon)Terhadap Inhibisi Protein Tubulin Homolog Pada Anti Kanker Dengan Molecular Docking Pyrx - fakhmi, nurul; , Dr. Muhammad Da'i, M.Si., Apt (2016)
2,5-bis (4-hydroxy-3-Methoxybenzylidene)-cyclopentanone and 2,5-bis (4-hydroxy-3,5-dimethyl)-benzylidenecyclopentanone were compounds that had known better anticancer activity than curcumin but lack of polarity. Through esterification in -OH groups, the polarity of these compounds can be improved. The aims to determine the effect of esterification on increasing activity of the inhibition of tubulin protein by molecular docking method. Homologs of tubulin protein were prepared and validated using PyRx-Vina Autodock. Ligands of test used were 2,5-bis (4-acetyloxy-3-Methoxybenzylidene) -cyclopentanone and 2,5-bis (4-acetyloxy-3,5-dimethyl)-benzylidenecyclopentanone. Ligands of standard used were 2,5-bis (4-hydroxy-3-Metoxybenzylidene)-cyclopentanone and 2,5-bis (4-hydroxy-3,5-dimethyl)-benzylidenecyclopentanone, Curcumin, Vinkristine, Vinblastine and ligand of mimics as many as 200 compounds. Molecular docking of ligands were performed using Vina and Autodock through methods of Lamarckian Genetic Algorithm (LGA), Genetic Algorithm (GA) and Simulated Annealing (SA), then analyzed using PLIP. The results showed that the sequence of binding affinity of ligands (small to large) as follows 2,5-bis (4-acetyloxy-3,5-dimethyl)-benzylidene-cyclopentanone; 2,5-bis (4-hydroxy-3,5-dimethyl)-benzylidene-cyclopentanone; 2,5-bis (4-acetyloxy-3-Methoxybenzylidene)-cyclopentanone; 2,5-bis (4-hydroxy-3-Metoxybenzylidene)-cyclopentanone; curcumin; vinblastine; and Vinkristine. Therefore it can be concluded that esterification lead to increase anticancer activity through decrease binding affinity and binding energy and increase amino acid interaction.